THE CORRELATION BETWEEN STUDENTS’ VOCABULARY AND TENSES MASTERY WITH THEIR WRITING ABILTY - Nurchurifiani, Eva (Lentera: Jurnal Ilmiah Kependidikan, 2018)
The correlation between students’ vocabulary and tenses mastery with their writing ability is interesting to be investigated. The writer took this title of the research because the writer found that the students’ writing ability need to be improved because the lack of vocabulary and tenses mastery. The objectives of this research were to know and described the correlation between students’ vocabulary and their writing ability, to know and described the correlation between students’ tenses mastery and their writing ability, to know and described the correlation between students’ vocabulary and tenses mastery with their writing ability. In this research the writer used descriptive quantitative method. The writer took 40 students’ as the sample from 205 students as the population. The population was the students’ of the eight class at MTs Al-Ikhlas Tanjung Bintang Lampung Selatan in 2015/2016. In getting the sample the writer used Stratified Proporsional Random Sampling Technique. To get the data vocabulary and tenses the writer used objectives test that was multiple choice contains 50 questions and 40 question. To get the data of writing test the writer used essay text. The writer used scoring system proposed by Heaton. Based on the data analysis, it was found that there is correlation between students’ vocabulary and tenses mastery with their writing ability the result showed that the level of the correlation is high, rcount = 0.91 with n:40 higher than rtable = 0.312, which has been counted on product moment table at significance level 5%. The writer concludes there is correlation between students’ vocabulary and tenses mastery with their writing ability of the eight class at Mts Al-ikhlas Tanjung Bingtang Lampung Selatan in 2015/2016.